Terahertz binary coder based on graphene metasurface - Gong, Yumin; Hu, Fangrong; Jiang, Mingzhu; Zhang, Longhui; Zou, Yingchang; Jiang, Guobao; Liu, Yongchen (Carbon (New York), 2021)
In this paper, we demonstrate a terahertz (THz) binary encoder based on graphene metasurface. The unit cell of the device consists of two parallel metal bars and two split-ring resonators (SRRs) embedded with two graphene ribbons. For two SRRs in the unit cell, one is connected to an electrode on the right side, and the other is connected to the electrode on the left side of the device, respectively. When no voltage is applied, the device has two passbands whose central frequencies locating at 0.85 THz and 1.14 THz, respectively. Unlike many THz tunable filters which modulate the amplitude of different bands at the same time, this encoder can achieve separately modulation of each passband. By electrically adjusting the Fermi energy of graphene on each SRR individually, the maximum modulation depth at the two central frequencies can be up to 80% and 87%, respectively. Furthermore, the function of THz frequency range binary coding is realized, i.e., four different binary coders of 11, 10, 01 and 00 are obtained in the transmission. Our work paves a new way for the development of multifunctional integrated THz devices, which will be of great significance in THz switching, communication and one-chip integrated THz system. We demonstrate a terahertz (THz) binary encoder based on graphene metasurface. The unit cell of the device consists of two parallel metal bars and two split-ring resonators (SRRs) embedded with two graphene ribbons. For two SRRs in the unit cell, one is connected to an electrode on the right side biased by voltage of U1, and the other is connected to the left electrode biased by voltage of U2, respectively. When no voltage is applied, the device has two passbands whose central frequencies locating at 0.85 THz and 1.14 THz, respectively. This encoder can achieve separately modulation of each passband. By electrically adjusting the Fermi energy of graphene on each SRR individually, the maximum modulation depth at the two central frequencies can be up to 80% and 87%, respectively. Furthermore, the function of THz frequency range binary coding is realized, i.e., four different binary coders of 11, 10, 01 and 00 are obtained in the transmission. Our work paves a new way for the development of multifunctional integrated THz devices, which will be of great significance in THz switching, communication and one-chip integrated THz system. [Display omitted]